Progress in the molecular phylogeny of Cotesia acuminata and C. melitaearum cryptic species complexes - Julian Schach; Federica Valerio; Anne Duplouy (PLoS ONE, 2026)
Cryptic species present major challenges for biodiversity and evolutionary research due to the morphological similarity and frequent lack of available genetic and ecological data. In parasitoid wasps, this is especially true for lineages with limited taxonomic and genetic sampling and unclear geographic ranges. Here we reconstruct the phylogeny of Cotesia wasps parasitizing Melitaeini butterflies, including two cryptic species complexes ( Cotesia acuminata agg . and C. melitaearum agg . ). Using a ten-gene dataset from samples collected in Europe, Asia, and North America, we inferred relationships among 22 Cotesia species using maximum likelihood. We also included non-Melitaeini associated Cotesia to assess whether the parasitoids of Melitaeini form a monophyletic group. Our analyses yielded a highly supported phylogeny, revealing four major clades, three of which included the Melitaeini associated species. This confirms that the Cotesia parasitizing Melitaeini butterflies are polyphyletic, likely resulting from independent host shifts across the genus. Each clade is further subdivided into subclades corresponding to the different cryptic species complexes, clarifying previously unresolved relationships. These results provide a robust framework for future studies on the evolution, ecology, and host use dynamics of Cotesia wasps and highlight the utility of multi-locus data for resolving phylogenies in morphologically cryptic taxa.